2019
DOI: 10.1371/journal.pone.0213963
|View full text |Cite
|
Sign up to set email alerts
|

An abscisic acid (ABA) homeostasis regulated by its production, catabolism and transport in peanut leaves in response to drought stress

Abstract: ABA is an important messenger that acts as a signaling mediator for regulating the adaptive response of plants to drought stress. Two production pathways, de novo biosynthesis and hydrolysis of glucose-conjugated ABA by β-glucosidase (BG), increase cellular ABA levels in plants. ABA catabolism via hydroxylation by 8’-hydroxylase (CYP707A), or conjugation by uridine diphosphate glucosyltransferase (UGT), decreases cellular ABA levels. The transport of ABA through ATP-binding cassette (ABC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 65 publications
0
15
1
Order By: Relevance
“…NCED genes catalyze the synthesis of xanthoxin, which is converted to abscisic aldehyde by short-chain alcohol dehydrogenase/reductase (SDR/ABA2) and then to ABA by abscisic aldehyde oxidase (AAO3). The molybdenum cofactor sulfurase/ABA3 is required by aldehyde oxidase for its activity (Long et al, 2019). However, as ABA2, ABA3, and AAO3 play only minor roles in ABA biosynthetic pathway (Ma et al, 2018), their transcript levels were not significantly increased in HDA15 OE plants (Figure 8).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…NCED genes catalyze the synthesis of xanthoxin, which is converted to abscisic aldehyde by short-chain alcohol dehydrogenase/reductase (SDR/ABA2) and then to ABA by abscisic aldehyde oxidase (AAO3). The molybdenum cofactor sulfurase/ABA3 is required by aldehyde oxidase for its activity (Long et al, 2019). However, as ABA2, ABA3, and AAO3 play only minor roles in ABA biosynthetic pathway (Ma et al, 2018), their transcript levels were not significantly increased in HDA15 OE plants (Figure 8).…”
Section: Discussionmentioning
confidence: 97%
“…However, as ABA2, ABA3, and AAO3 play only minor roles in ABA biosynthetic pathway (Ma et al, 2018), their transcript levels were not significantly increased in HDA15 OE plants (Figure 8). In addition, the higher accumulation of ABA in HDA15 OE plants may be due to BG2 upregulation, which catalyzes inactive ABA-GE to ABA in one-step hydrolysis (Long et al, 2019). Induction of BG2 also helps plants to quickly enhance internal ABA levels for stress adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Target gene LOC112730895 of hub lncRNA MSTRG.41333.1 encodes ABC transporter C family member 15 (Figure 6a). It was reported that ABA homeostasis contributes to drought tolerance through a balance between the production, catabolism and transport in peanut leaves [45]. Target gene LOC112726802 of hub lncRNA MSTRG.47603.1 encodes BON1-associated protein 2, which is a plasma membrane-localized protein, plays a negative role in regulating the expression of immune receptor genes, but has a positive regulation in stomatal closure [46].…”
Section: Discussionmentioning
confidence: 99%
“…As a stress hormone, abscisic acid (ABA) is involved in the response to various adverse environmental factors, particularly to drought, through the regulation of specific signalling pathways and the modification of gene expression levels [ 7 , 8 , 9 , 10 , 11 ]. Under drought, ABA controls water loss through stomata closure, transpiration flux reduction, a decrease in water potential (ψ), and a reduction in leaf area [ 12 ].…”
Section: Introductionmentioning
confidence: 99%